The effects of state-subsidised housing on poverty in Cape Town. Issue 5 (2nd September 2016) - Muyeba, Singumbe
ABSTRACT: Property rights are widely thought to have considerable direct and indirect effects on urban poverty. However, few studies have been conducted and the evidence supporting these claims is scarce, especially in Southern Africa. This article examines effects of property rights in South Africa through a case study of subsidised housing for poor people in Khayelitsha, Cape Town. A difference-in-differences estimation strategy is employed. Results show that housing subsidies are associated with better physical health and (counter-intuitively) more teenage pregnancies. Improvement in health is attributed to better housing quality and environment while increase in teenage pregnancies is attributed to increased privacy. Effects of titling extend to social effects, which have been understudied in the literature. Since titling showed no effect by most measures, it is likely that poverty is driven so strongly by factors such as unemployment and poor location of housing projects that property rights make little overall difference to poverty.